Preparation of Al2O3 /PVA Nanocomposite Thin Films by a Plasma Jet Method - Saba Jawad Kadhem (Science and Technology Indonesia, 2023)
Alumina thin films have significant applications in the areas of optoelectronics, optics, electrical insulators, sensors and tribology. The novel aspect of this work is that the homogeneous alumina thin films were prepared in several stages to generate a plasma jet. In this paper, aluminium nanoparticles suspended in vinyl alcohol were prepared using exploding wire plasma. TEM analysis was used to determine the size and shape of particles in aluminium and vinyl alcohol suspensions; the TEM images showed that the particle size is 17.2 nm. Aluminium/poly vinyl alcohol (Al/PVA) thin films were prepared using this suspension on quartz substrate by plasma jet technique at room temperature with an argon gas flow rate of 1 L/min. The Al/PVA thin films were thermally converted to alumina films, where they were annealed at different temperatures (700, 800, or 900°C). X-ray diffraction (XRD), atomic force microscopy (AFM), transmission electron microscopy (TEM), scanning electron microscopy (SEM), and Fourier transform infrared spectroscopy (FTIR) techniques were used to characterise these thin films before and after annealing process. The diffraction patterns of the prepared thin films before subjecting them to the annealing process indicated the presence of peaks belonging to aluminium and PVA; however, the diffraction patterns and FTIR spectra obtained for these films after the annealing process showed peaks indicating the formation of alumina films of different phases. AFM and SEM investigations proved that the formed particles for all prepared films before and after the annealing process were similar in size and almost spherical; the diameter of the particles was on the order of a few nanometres. To control the properties of prepared thin films, the plasma which was used to produce thin films is diagnosed spectrophotometrically. The generated plasma was diagnosed using optical emission spectroscopy to estimate the electron temperature Te; the electron temperature was 1.925 eV.